2020
DOI: 10.1038/s41597-020-0515-6
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: A global database of Holocene paleotemperature records

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Our study completes the southern end of a N-S transect of paleoclimate records in Yakutia (Figure 9) established by multiple studies along the Lena River over the last decades (Laing et al, 1999;Andreev et al, 2004;Fradkina et al, 2005;Popp, 2006;Müller et al, 2009;Biskaborn et al, 2012;Klemm et al, 2013;Nazarova et al, 2013;Tarasov et al, 2013;Biskaborn et al, 2016;Kostrova et al, 2021). The Holocene warming trend in Siberia is a common and very clear feature reflecting the glacial-interglacial transition in the Northern Hemisphere (Kaufman et al, 2020). However, previous investigations of lake records along the transect showed that the onset of most pronounced warming within the interglacial lagged by up to ∼3 kyrs in southern direction (Biskaborn et al, 2012), contradicting the assumption that warming was primarily related to solar insolation (Bond et al, 2001;Miller et al, 2010).…”
Section: Bolshoe Toko As the Southern End Of A North-south Paleoclimate Transect In Siberiasupporting
confidence: 76%
See 1 more Smart Citation
“…Our study completes the southern end of a N-S transect of paleoclimate records in Yakutia (Figure 9) established by multiple studies along the Lena River over the last decades (Laing et al, 1999;Andreev et al, 2004;Fradkina et al, 2005;Popp, 2006;Müller et al, 2009;Biskaborn et al, 2012;Klemm et al, 2013;Nazarova et al, 2013;Tarasov et al, 2013;Biskaborn et al, 2016;Kostrova et al, 2021). The Holocene warming trend in Siberia is a common and very clear feature reflecting the glacial-interglacial transition in the Northern Hemisphere (Kaufman et al, 2020). However, previous investigations of lake records along the transect showed that the onset of most pronounced warming within the interglacial lagged by up to ∼3 kyrs in southern direction (Biskaborn et al, 2012), contradicting the assumption that warming was primarily related to solar insolation (Bond et al, 2001;Miller et al, 2010).…”
Section: Bolshoe Toko As the Southern End Of A North-south Paleoclimate Transect In Siberiasupporting
confidence: 76%
“…Over the past few decades, boreal and high elevation regions warmed faster than elsewhere (Mountain-Research-Initiative et al, 2015) and was strongest in northern Russia (Biskaborn B. K. et al, 2019). Although the Siberian region is generally regarded as being underrepresented in paleoenvironmental research (Sundqvist et al, 2014;Mckay et al, 2018;Kaufman et al, 2020), there is an ever-expanding interest in the area due to expected environmental changes and associated strong socioenvironmental implications (Amap, 2017). In particular, remote Arctic lakes in permafrost regions represent pristine earlywarning systems of environmental change, as they rapidly respond to climatic perturbations and changes in geoecological boundary conditions in their catchments (Subetto et al, 2017;Biskaborn et al, 2021;Nazarova L. B. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, quantitative indicators of past temperature (hereafter called “proxies”) based on different types of archives have been used to reconstruct climate variability over a range of timescales. The improvement of both spatial coverage and temporal resolution of temperature proxy records led to the development of regional and global temperature reconstructions, which have allowed the scientific community to highlight the unprecedented nature of anthropogenic climate change across the common era 1 , 2 and the Holocene 3 6 . Global temperature reconstructions consistently depict a Holocene Thermal Maximum (HTM) typically ranging between 10 and 5 ka 4 , 5 with a maximal probability centered around 6.45 ka 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, model-data inconsistencies may equally well result from geographically divergent trends due to sea-ice dynamics 9 , polar amplification 10 , insufficient model resolution 11 , and boundary conditions used in numerical simulations 12 . Although the HTM has been intensively studied from a global perspective 3 7 , its spatio-temporal characteristics have received relatively little attention, even though the local and regional trends differ markedly from the globally averaged reconstructions 3 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…For the period before the late nineteenth century, when colonial states established weather stations with reliable meteorological instruments across their growing territories, our knowledge of past climate comes primarily from proxy data in the archives of nature. Examples of proxy records include the annual rings of trees, the geochemistry of cave formations and coral skeletons, the composition and contents of polar and high-altitude glaciers and ice sheets, and the organic and inorganic components of lake and ocean sediments (figure 1) (Baumgartner et al 1989, Jones et al 2009, Bradley 2014, Kaufman et al 2020b.…”
Section: Reconstructing Climate Changementioning
confidence: 99%